GAGASAN INTEGRASI KEWENANGAN OMBUDSMAN DAN LEMBAGA HAM MELALUI STUDI KOMPARASI KELEMBAGAAN OMBUDSMAN REPUBLIK INDONESIA DAN THE PARLIAMENTARY OMBUDSMAN OF FINLAND - Puspitaningrum, Hani; Husodo, Jadmiko Anom (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
The aim of this research is to acknowledge about similarities and differences between the institutions of Ombudsman Republik Indonesia and The Parliamentary Ombudsman of Finland. As the result of doing comparative study then obtained the things that can be adopted to overcome the weakness and optimize the existence of Ombudsman Republik Indonesia. This writing is a normative legal research which is classified as prescriptive and applied research. The approaches used in this legal research are comparative, statutes, conceptual and historical approaches. This legal research uses primary, secondary legal materials and also nonlegal materials. Legal materials collected by study the literatures, then furtherly analyzed by using deductive techniques and so does the reasoning method. The results showed that the comparison between the two institutions of the Ombudsman there are similarities and differences between the Ombudsman Republik Indonesia and The Parliamentary Ombudsman of Finland. From the differences there are some simillarities that can be transplanted to overcome some weaknesses that occur in Indonesia. The things that will be transplanted are not entirely relevant to the existing conditions in Indonesia caused by several factors that can be classified as supporting factors (opportunities) and inhibiting factors (obstacles) and also the logical consequences if the Finnish model is going to be implemented in Indonesia